2019
DOI: 10.1136/bmjopen-2018-025367
|View full text |Cite
|
Sign up to set email alerts
|

What does it take to provide clinical interventions with temporal consistency? A qualitative study of London hyperacute stroke units

Abstract: ObjectivesSeven-day working in hospitals is a current priority of international health research and policy. Previous research has shown variability in delivering evidence-based clinical interventions across different times of day and week. We aimed to identify factors influencing such variations in London hyperacute stroke units (HASUs).DesignInterview and observation study to explain patterns of variation in delivery and outcomes of care described in a quantitative partner paper (Melnychuk et al).SettingEight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…However, for other less time-critical measures, such as senior stroke physician assessment within 24 hours and therapist assessments within 72 hours, we found significant variation by day and time of admission across the week in London HASUs. This suggests that some performance standards like ‘front door’ interventions may be emphasised more than others and analysis of qualitative data collected in Black et al 39 complemented our findings 39. The second implication is that there are differences in acute stroke care between London HASUs and the rest of England across the week, with less variation in quality of care and outcomes in London HASUs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, for other less time-critical measures, such as senior stroke physician assessment within 24 hours and therapist assessments within 72 hours, we found significant variation by day and time of admission across the week in London HASUs. This suggests that some performance standards like ‘front door’ interventions may be emphasised more than others and analysis of qualitative data collected in Black et al 39 complemented our findings 39. The second implication is that there are differences in acute stroke care between London HASUs and the rest of England across the week, with less variation in quality of care and outcomes in London HASUs.…”
Section: Discussionsupporting
confidence: 64%
“…What our study adds is analyses of variation in quality of care and outcomes in London HASUs separately following the centralisation of acute stroke services in London in 2010, which has been shown to increase the quality of care and outcomes on average across the week 29 30. Our findings were further expanded in Black et al 39 that aimed to identify factors influencing this variation 39…”
Section: Discussionmentioning
confidence: 84%
“…There may be lessons to learn from the centralization of acute stroke services in London, which alleviated the effect of the day and time of admission on brain imaging and thrombolysis 40 . A strong relationship with the radiology department has been considered as one of the reasons for the success of this initiative 41 . Increased access to imaging resources would also facilitate the quick progress of the patient with CLTI through the diagnostic pathway, whereas redistribution of imaging as well as cardiorespiratory test slots to correlate with the variation in demand may alleviate this disparity in waiting times.…”
Section: Percentage Of Revascularised Patientsmentioning
confidence: 99%
“…We have previously published findings about how stroke services produce consistent outcomes despite variation in staffing and resources and the unintended consequences 12 13. This revealed that services must deploy their efforts disproportionately on those aspects that have the greatest impact on clinical outcomes, employing strategies such as stretching junior staff roles at night to achieve consistency 12.…”
Section: Introductionmentioning
confidence: 99%